The vaccination coverage rate in under-5 children in Nasiriyah, Iraq before and during the COVID-19 pandemic - Ali Rifaat Alhaddad; Elham Ahmadnezhad; Akbar Fotouhi (Epidemiology and Health, 2022)
OBJECTIVES This study compared the vaccination coverage rate (VCR) in children under 5 years old in Nasiriyah, Iraq before and during the coronavirus disease 2019 (COVID-19) pandemic. METHODS This cross-sectional study was conducted in the city of Nasiriyah in southeastern Iraq, with data collected from 79 primary healthcare facilities. This study evaluated the VCR in 3 periods (2018, 2019, and 2020) using multi-level random sampling. Pertinent data were extracted from the vaccination records of 598 children for Bacillus Calmette-Guérin (BCG); pentavalent 1, 2, and 3; measles; and activated oral poliovirus vaccine 1 and 2. Missing data were completed by telephone calls to participants’ parents. Logistic regression was applied to compare and estimate the odds ratios (ORs) with 95% confidence intervals (CIs) for the association between VCR and related factors. RESULTS The data showed the greatest decline in the studied vaccines in 2020. Among the vaccines studied, BCG had the highest rate in all 3 periods (100% VCR) and measles had the lowest rate (83.7%), reaching 63.6% in 2020 (p<0.001). The highest OR among all types of vaccine were found for the pentavalent-3 vaccine among city dwellers and those born in 2020 (OR, 2.67; 95% CI, 1.39 to 5.10 and OR, 2.34; 95% CI, 1.28 to 4.28, respectively). CONCLUSIONS The VCR for children decreased during the COVID-19 pandemic in Iraq, and new health policies are needed to increase the coverage rate. Improving the knowledge and attitudes of parents, as well as removing barriers or risk factors, can also be effective in improving the VCR.